Eliminating Healthcare-Associated Infections in Iran: A Qualitative Study to Explore Stakeholders' Views - Atefeh Esfandiari; Hedayat Salari; Arash Rashidian; Hossein Masoumi Asl; Abbas Rahimi Foroushani; Ali Akbari Sari (Kerman University of Medical Sciences, 2018)
Background Although preventable, healthcare-associated infections (HAIs) continue to pose huge health and economic burdens on countries worldwide. Some studies have indicated the numerous causes of HAIs, but only a tiny literature exists on the multifaceted measures that can be used to address the problem. This paper presents stakeholders' opinions on measures for controlling HAIs in Iran. Methods We used the qualitative research method in studying the phenomenon. Through a purposive sampling approach, we conducted 24 face-to-face interviews using a semi-structured interview guide. Participants were mainly key informants, including policy-makers, health professionals, and technical officers across the national and subnational levels, including the Ministry of Health (MoH), medical universities, and hospitals in Iran. We performed thematic framework analysis using the software MAXQDA10. Results Four main interdisciplinary themes emerged from our study of measures of controlling HAIs: strengthening governance and stewardship; strengthening human resources policies; appropriate prescription and usage of antibiotics; and environmental sanitation and personal hygiene. Conclusion According to our findings, elimination of HAIs demands multifactorial interventions. While the ultimate recommendation of policy-makers is to have HAIs among the priorities of the national agenda, financial commitment and the creation of an enabling work environment in which both patients and healthcare workers can practice personal hygiene could lead to a significant reduction in HAIs in Iran.